TASAWUF : Sejarah, Madzhab, dan Inti Ajarannya - Aly Mashar (UIN Raden Mas Said Surakarta, 2015)
The study aims to describe tasawuf, which is focusing on thedevelopment history, various madzhab, and its teaching cores. Thedevelopment of tasawuf has divided into five periodes: formation,development, consolidation, philosophical, and purification. Within itsdevelopment‟s history tasawuf has three main madzhab with theirrespective loyal followers. All of those madzhab have agreed that themain teaching of tasawuf is cleaning the sould to be able to be closedto God with the certain methods. Those mazhabs have differentopinions on the form of the method, stage of maqamat, and theexistence of ahwal.